Fixing STEM Workforce and Teacher Shortages: How Goal Congruity Can Inform Individuals and Institutions. (March 2018) - Diekman, Amanda B.; Benson-Greenwald, Tessa M.
As demands increase for individuals with expertise in science, technology, engineering, and mathematics (STEM), educational institutions and workplaces seek to identify strategies to recruit and retain talented individuals in STEM pathways. We investigate recruitment and retention into the STEM workforce and into primary and secondary STEM education careers by analyzing whether a particular role allows an individual to fulfill goals. The two occupational pathways reviewed here pose different goal congruity challenges: The STEM workforce seems to lack communal (other-oriented) goal opportunities, but math and science K-12 teaching seems to lack agentic (self-oriented) goal opportunities. Restructuring educational and occupational roles to maximize the pursuit of valued goals can encourage STEM recruitment and retention.